Morphological Impacts due to Storms on a Macro-Tidal Beach - William Bennett (Coastal Dynamics 2017, 2017)
A set of storms, with varying intensity and duration, was used to investigate the range of morphological impacts on a macro-tidal beach (Sefton coast, Liverpool Bay, UK), using a nested computational modelling framework. Extreme wave and water level conditions were extracted from modelled and observed data corresponding to a range of return periods, and fitted to a storm profile to provide real time offshore boundary forcing. The peak water level was found to be the main driving force in defining the bed evolution, with the strongest changes along the northern part of the Sefton coast. Breaching of the dune crest was observed in storms with a peak water level greater than the current 1 in 50 year return level. The simulation of beach evolution during storms provides very useful insights in to the morphodynamic processes, and also, provides information to improve existing coastal management strategies.